Association between the dietary inflammatory index and common mental health disorders profile scores. Issue 4 (August 2019) - Haghighatdoost, Fahimeh; Feizi, Awat; Esmaillzadeh, Ahmad; Feinle-Bisset, Christine; Keshteli, Ammar Hassanzadeh; Afshar, Hamid; Adibi, Payman
Summary: Background & aims: The association between diet and mental health disorders might be mediated by inflammatory properties of the diet. We evaluated the association between the dietary inflammatory index (DII) and the risk of a worsened mental health disorders profile. Methods: A total of 3363 Iranian adults were included in this cross-sectional study. A mental health disorders profile score was calculated using regression analysis, within the framework of factor analysis, based on anxiety, depression and psychological distress, with a higher scores indicating greater severity of mental problems. Dietary intakes were assessed using a validated dish-based food frequency questionnaire (DFQ). Twenty-seven macro- and micro-nutrients, onions, tea and caffeine were included in the calculation of DII. Each of them received a score based on their inflammatory ability, thus, a greater DII indicated a more pro-inflammatory diet. The odds of being in the highest tertile of mental health disorders profile across the tertiles of DII was assessed using multinomial logistic regression. Results: Either in the crude or fully-adjusted multinomial logistic regression models, participants in the lowest tertile of DII had a lower risk for being in the top tertile of mental health disorders profile (adjusted model: OR: 0.45; 95% CI: 0.33, 0.60; P trend<0.001). In a stratified analysis by sex, similar findings were observed in both genders, although there was only a trend for the associations to be significant in men (men: OR: 0.53; 95% CI: 0.31, 0.90; P trend = 0.070; women: OR: 0.40; 95% CI: 0.27, 0.58; P trend<0.0001). Conclusions: Our findings suggest a direct association between the pro-inflammatory properties of the diet and an increased risk of higher mental health disorders profile scores. Prospective dietary intervention studies and observational prospective cohorts are required to confirm these findings. Highlights: A pro-inflammatory diet is associated with increased risk of higher mental health disorders profile scores. Higher DII scores are associated with increased risk of mental disorders in both genders with greater risk in women. Intervention and prospective observational studies are suggested for confirming our results.